Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences, 2021)
This issue of KIU Journal of Social Sciences focuses on Development Administration, Political Education, Educational Social Psychology as well as Peace and Conflict Studies. The first part of the Journal addresses issues in Development Administration such as Rural Development, Human Resource Practice, Democratic Governance, Demographic Changes, Women Empowerment and so on. It is argued in one of the papers that that urbanization is very significant in reducing unemployment in the rural areas and promoting economic growth, therefore its importance should not be exaggerated. The study recommends that Sub Sahara African countries should put urbanization at the heart of their socio-economic policies and programmes so that it can extend economic opportunities and potentials to the rural areas, which will serve as impetus for rapid economic growth of the Sub Sahara African countries. Section two explores issues in Political Education such as Usage of Media Advocacy Election, Voting Behaviour, Elite Self Recruitment, Party Defection and Consolidation of Democracy. Based on its findings, one of the papers argues that since party defections are not driven by fundamental ideological considerations, the outcome is an unstable opposition which is unable to sustain and consolidate the gains of democracy. The paper, thererfore, recommends that party manifestoes be supreme with laws made to limit defections. Elected representatives should also lose their seats if they defect outside the procedure to be provided for in the electoral act. The third section deals with Peace and Conflict Resolution Strategies. Relying on an emipirical study, one of the research papers in this section argues that despite the equal inclination of religion to peace and conflict, it is more prone to conflict than peace, especially because of its inherent proneness to segregation and manipulation. The paper, therefore, recommends a general re-orientation of all stakeholders of peace and conflict in relation to the role of religion in the society, following the realist, rather than the utopian, claims that help maintain the unwanted influence of religion on the balance of peace and conflict in human society.  According to the paper, this re-orientation is necessary because it will help clear the scholarly confusions on ground and to place religion in its rightful place in the promotion of the necessary balance of peace and conflict in human society. Papers in the last section are on Educational Social Psychology. Using focus group discussion method to elicit relevant information, including key informant interview with the students, teachers and parents of Essence Secondary School, at 10 Kashim Ibrahim Road in Kaduna metropolis, one of the papers in these sections reveals that television viewing does take away from credible academic performance, as well as influence behaviors and actions of the students. In all, this issue of KIU Journal of Social Sciences features many educative and interesting research papers which are very useful to all and sundry.